The Acceptance and Implementation of the Rules for Archival Description by Canadian Archives: A Survey - Duff, Wendy (Archivaria, 1999)
The first chapters of RAD were published only nine years ago, but many observers suggest that most Canadian archives have accepted and use RAD. This article reports on a survey that investigated the use of RAD in Canada. It furthermore presents information concerning the state of RAD implementation, including the levels to which archives use RAD in their descriptive systems, the extent to which authority files and data structure standards are employed, and the types of support documentation created. The article also provides information about who does description, the training they have received, and the barriers to adoption of RAD. The results indicate that there is astrong relationship between the use of RAD, description undertaken at higher levels (for example, fonds), and the involvement of professionals in descriptive work. The article concludes with suggestions for future research. RÉSUMÉ Les premiers chapitres des RDDA ont été publiés il y a seulement neuf ans; mais selon plusieurs observateurs, la plupart des services d’archives canadiens les ont acceptées et les utilisent. Cet article traite d’une enquête qui a porté sur l’utilisation des RDDA au Canada. Il aborde l’état actuel de l’implantation des RDDA en examinant les niveaux d’utilisation des Règles au sein des systèmes descriptifs des dépôts d’archives, dans quelle mesure on utilise des fichiers d’autorité et des structures de données normalisées et quels sont les types de supports documentaires créés. L’article pose la question de qui prépare les descriptions, la formation que ces personnes ont reçue et les obstacles freinant l’adoption des RDDA. Les résultats montrent qu’il y a un rapport étroit entre l’utilisation des Règles, les descriptions réalisées aux plus hauts niveaux (par exemple celui du fonds) et l’implication de professionnels dans le travail de description. L’article propose en conclusion des pistes pour d’autres recherches.